Contribution of live fences to the ecological integrity of agricultural landscapes - Harvey, C.A. (2005)
Live fences are conspicuous features of agricultural landscapes across Central America but there is remarkably little information about their abundance, distribution, and function. Here we present a detailed analysis of: (1) the abundance, composition, structure and distribution of live fences in four contrasting cattle-producing areas of Costa Rica and Nicaragua; (2) the management of live fences by farmers; and (3) the ecological roles of live fences in providing habitat, resources and connectivity for wildlife. Data on botanical composition and structure are complemented by documentation of local knowledge about live fences and associated management practices, as well as an assessment of fauna that utilize them. Live fences were common, occurring on between 49% and 89% of cattle farms, with an overall mean of 0.14 0.01 km ha 1 of farm land and almost 20 fences per farm. They were generally short (164.3 5.4 m), narrow (3.76 0.03 m) and densely planted (323.1 8.6 trees km 1 ), consisting primarily of planted trees. The mean tree species richness for individual fences in each landscape was low (from 1.4 to 7.5 species per fence), but landscape species richness was higher (from 27 to 85 species, with over 70 species in three out of four sites). A total of 161 tree and palm species were recorded in the live fences across the four sites. The abundance, tree species composition and structure of live fences varied across farms and landscapes, reflecting differences in environmental conditions and management strategies. In all landscapes the main productive roles of live fences were to divide pastures and serve as barriers to animal movement, although they were also sources of fodder, firewood, timber and fruit. The main ecological roles were to provide habitats and resources for animal species and structural connectivity of woody habitat across the agricultural landscape. More than 160 species of birds, bats, dung beetles and butterflies were recorded visiting them. Their value for biodiversity conservation depended on their species composition, structural diversity and arrangement within the landscape, all of which were heavily influenced by management currently undertaken by farmers in pursuit of production rather than conservation goals. Live fences are important features of agricultural landscapes that merit much greater attention in sustainable land management strategies and need to be an explicit element in regulations and incentives that aim to enhance the ecological integrity of rural landscapes in Central America. # 2005 Elsevier B.V. All rights reserved.